2020
DOI: 10.4025/actasciagron.v43i1.46712
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis for the root distribution trait in common bean

Abstract: Heterosis has been one of the most studied phenomena since genetic studies were conceived. Knowledge of this phenomenon for the root distribution trait in beans (Phaseolus vulgaris L.) can favour the development of genotypes that are more tolerant to abiotic stresses. This study aimed to verify the occurrence of heterosis for the root distribution trait in hybrid F1 populations of common bean derived from crosses within and between gene groups. Thirty-six populations (six parents and 30 hybrids) were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In common bean, based on the complete diallel cross design, comparisons between the means of the parents and those of the segregating generations supported the assumption of predominant additive inheritance of the trait root distribution (de Melo et al, 2016(de Melo et al, , 2018. In addition, it has been found that heterosis is not fundamental for root distribution, even when plants of different gene groups of common bean are crossed; the authors suggested that possible epistatic effects influence this trait (Grigolo et al, 2021). Likewise, a study on the inheritance of common bean root distribution reported significant additive x additive epistatic effects, with consequent implications for plant selection (Araújo et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…In common bean, based on the complete diallel cross design, comparisons between the means of the parents and those of the segregating generations supported the assumption of predominant additive inheritance of the trait root distribution (de Melo et al, 2016(de Melo et al, , 2018. In addition, it has been found that heterosis is not fundamental for root distribution, even when plants of different gene groups of common bean are crossed; the authors suggested that possible epistatic effects influence this trait (Grigolo et al, 2021). Likewise, a study on the inheritance of common bean root distribution reported significant additive x additive epistatic effects, with consequent implications for plant selection (Araújo et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…A ausência de significância entre genótipos de feijão advindos de esquemas de hibridações para distribuição radicular já foi relatada (De Melo et al, 2016;Grigolo et al, 2021).…”
Section: Resultsunclassified
“…In this research, due to the insu cient amount of seeds, the F 1 populations were not planted either. However, this progeny had been evaluated for the same traits in the eld in the previous two years (Cerutti et al 2020;Grigolo et al 2021). In those experiments, 30 different F 1 hybrid combinations as well as the F 2 progenies and parents had been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the progress of breeding programs in selecting progenies with a satisfactory root development has been slow, since other, shoot-related traits are prioritized (Tracy et al 2020). For common bean, the presence of transgressive segregants has been reported as an exception rather than the rule (Toaldo et al 2013;de Melo et al 2016;Grigolo et al 2021). Of the few progenies detected, a signi cant portion was found to have an inferior performance to the parents (Cerutti et al 2020;Grigolo et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation